CONSUMER PROTECTION CONCERNING CIRCULATION OF BULK COOKING OIL AFTER THE ISSUANCE OF REGULATION OF THE MINISTER OF TRADE OF THE REPUBLIC OF INDONESIA NUMBER 80/M-Dag/Per/10/2014 - Zahrul Fatahillah (STIS Nahdlatul Ulama Aceh, 2020)
After the issuance of the Trade Ministry Regulation No.80 / M-Dag / Per / 10/2014 on packaging compulsory of bulk cooking oil. Accordingly, bulk cooking oil labeling is required to guarantee consumer protection. Yet, until the enactment of the ministry Regulation in 2020 bulk cooking oil is still sold in the market, however this is very detrimental to consumers. The main problems in this study are (1) what is the form of consumer protection law against the circulation of bulk cooking oil without labels? (2) what is the responsibility of the businessmen and the legal consequences of the circulation of cooking oil without labels? The purpose of this study is to determine the form of legal protection, responsibility of businessmen and the legal consequences of the circulation of cooking oil without a label after the issuance of the Minister of Trade Regulation on mandatory cooking oil. The writer will apply normative legal research, a study that places norms as research objects. The results showed that there are still many businessmen who do not label cooking oil due to lack of strictness both the government and the existing rules, so that it is very detrimental to consumers. It is suggested to the government to keep socializing to consumers about their rights and the importance of consuming labelled cooking oil and to provide legal protection so that consumers feel safe and comfortable in consuming cooking oil.